Features of the enzyme composition of Jerusalem artichoke tubers - I. Bilenka (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького. Серія: Харчові технології, 2019)
The article deals with different methods of preparing Jerusalem artichoke tubers to stabilize the color of semi-finished products and finished products. The varieties Interés and Violet de Rennes were chosen as objects of study. The purpose of this work is to study the activity of the enzyme system of Jerusalem artichoke tubers, followed by the use of raw materials as an ingredient in the preparation of culinary dishes with high nutritional and biological value. In accordance with the objective, the characteristics of the enzymatic composition of the material under study were researched. It was found that of the oxidoreductases present, the most active enzyme is polyphenol oxidase. It has been established that in the tubers of Jerusalem artichoke, the activity of polyphenol oxidase is in 1.8 times lower, peroxidase – in 1.34 times higher; ascorbate oxidase is in 2.79 times higher than that of Violet de Rennes tubers. A comparative analysis was performed on the reduction of the activity of enzymes and the preservation of the mass fraction of L-ascorbic acid in heat treatment and microwave processing. It has been established that the most successful method of treating Jerusalem artichoke tubers in order to inactivate the enzyme system and to preserve L-ascorbic acid is a microwave processing of 600 W in 1 minute. Studies have shown that with such preparation, the semi-finished product does not change color, the activity of the enzyme polyphenol oxidase decreases by 20 times, and the maintenance of the content of L-ascorbic acid is 68.4%. In further studies, it is important to study the technologies for preparing culinary dishes based on Jerusalem artichoke tubers using the results obtained to stabilize the color and preserve the biologically active substances of the raw materials.